Caregivers with limited language proficiency and their satisfaction with paediatric emergency care related to the use of professional interpreters: a mixed methods study - Julia Brandenberger; Kristina Keitel; Jabeen Fayyaz; Myriam Gmünder; Noemi Gessler; Sina Buser; Ursula Feuz; Anne Jachmann (BMJ Open, 2024)
Objectives Communication is a main challenge in migrant health and essential for patient safety. The aim of this study was to describe the satisfaction of caregivers with limited language proficiency (LLP) with care related to the use of interpreters and to explore underlying and interacting factors influencing satisfaction and self-advocacy.Design A mixed-methods study.Setting Paediatric emergency department (PED) at a tertiary care hospital in Bern, Switzerland.Participants and methods Caregivers visiting the PED were systematically screened for their language proficiency. Semistructured interviews were conducted with all LLP-caregivers agreeing to participate and their administrative data were extracted.Results The study included 181 caregivers, 14 of whom received professional language interpretation. Caregivers who were assisted by professional interpretation services were more satisfied than those without (5.5 (SD)±1.4 vs 4.8 (SD)±1.6). Satisfaction was influenced by five main factors (relationship with health workers, patient management, alignment of health concepts, personal expectations, health outcome of the patient) which were modulated by communication. Of all LLP-caregivers without professional interpretation, 44.9% were satisfied with communication due to low expectations regarding the quality of communication, unawareness of the availability of professional interpretation and overestimation of own language skills, resulting in low self-advocacy.Conclusion The use of professional interpreters had a positive impact on the overall satisfaction of LLP-caregivers with emergency care. LLP-caregivers were not well—positioned to advocate for language interpretation. Healthcare providers must be aware of their responsibility to guarantee good-quality communication to ensure equitable quality of care and patient safety.